Trillin inhibits MAP3K11/NF-κB/COX-2 signaling pathways through upregulation of miR-145-5p in castration-resistant prostate cancer - Yanlong Wang; Yulin Peng; Wenjun Hao; Chengjian He; Xiang Gao; Peng Liang; Haolin Zhao; Ying Wang; Liang Wang; Zhenlong Yu; Zhiyu Liu (iScience)
Summary: Castration-resistant prostate cancer (CRPC) presents a significant challenge in treatment following androgen deprivation therapy. This study evaluates Trillin, a compound with antioxidant and anti-inflammatory properties, for its therapeutic potential against CRPC. Using DU145 and PC3 cell lines and a mouse xenograft model, we demonstrate that Trillin effectively inhibits CRPC cell viability, proliferation, migration, and invasion while promoting apoptosis and cell-cycle arrest. Mechanistic investigations reveal that Trillin disrupts NF-κB/COX-2 signaling by downregulating MAP3K11 and COX-2 and inhibiting the nuclear translocation of NF-κB subunits. Additionally, Trillin enhances the expression of miR-145-5p, further modulating pathways critical for CRPC progression. These findings suggest that Trillin may offer a promising alternative approach for targeting CRPC, highlighting its potential as a therapeutic agent to improve patient outcomes.